Implementation of Total Quality Management (TQM) in Efforts to Improve the Quality of Higher Education (Case Study at Gorontalo State University) - Sri Yulianty Mozin; Irina Popoi (AIBPM Publisher, 2018)
The study entitled Implementation of Total Quality Management (TQM) in Efforts to Improve the Quality of Higher Education (Case Study at Gorontalo State University) aims to describe (1) the stages of implementing TQM in universities; (2) the quality of Gorontalo State University. The method of this research is qualitative with the type of case study research. Data collection is done by in-depth interviewing techniques to informants and documentation studies. Data analysis techniques through data reduction, data presentation, verification and conclusion. The results of the study were: (1) the implementation of TQM at Gorontalo State University was carried out systematically through the stages of preparation, planning and implementation. In the preparatory stage, universities carry out initial design or internal reinforcement to recognize the potential of Gorontalo State University. Higher education has prepared well to carry out TQM implementation well. At the planning stage, the university has developed a long-term plan for effective management, using the PDCA cycle, namely the plan (plan preparation), do (plan implementation), check (review and evaluation), and act (follow-up completion). At the implementation stage, management or university leaders have realized strategies and policies into action through the activation of the team and the implementation of quality management projects properly. Higher education has established a pillar or acceleration of quality improvement well; (2) the quality of Gorontalo State University as the ability of tertiary institutions to implement the tri dharma of higher education has jumps in quality achievement. The rector of Gorontalo State University has prioritized acceleration of accreditation to support the acceleration of the realization of Leading University. The quality of tertiary institutions has achieved a lot of strategic goals and consistent achievement has been marked by obtaining institutional accreditation (University Accreditatiton 2018) with A grades, human resources acceleration and increasing professors and doctors, assessment of governance through the ranking of tertiary institutions at 47th rank collaboration with the world's best universities that work together in research, community service, natural resource management, and cultural promotion. Keywords: Total Quality Management, Quality, Higher Education.